Behaviors, Strategies and Achievement in Reading Comprehension in PISA: Analysis for Peru - Cueto, Santiago; León, Juan; Muñoz, Ismael G.; Rosales, Elizabeth (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
Learning to read is internationally considered a central goal of schooling. In this analysis we used data from PISA on reading comprehension for Peru, with the aim of determining if the socioeconomic characteristics of students are associated with their performance, behaviors and educational strategies, as well as with their school environment. Regarding educational resources for students in their homes and institutions, a positive gradient was found, which was associated with socioeconomic status. While the average reading performance of Peruvian students grew significantly between 2000 and 2009, students of lower socioeconomic status showed the lowest improvement. There are three pedagogical variables with high explanatory power in reading achievement: comprehension, synthesis and memory strategies (the first two with a positive sign, and the last one with a negative sign). We also found a strong association between classroom climate and reading performance in educational institutions of lower socioeconomic status. Our results suggest that students with lower socioeconomic status have lower levels of learning opportunities and lower performance. We suggest attention and investment in the educational institutions these students attend, as well as designing and evaluating the impact of interventions focusing on the pedagogical variables mentioned above.